Growth, Efficiency of Feed Utilization and Economics of Different Rearing Periods of Turkeys Mukesh Karki (Nepal Agriculture Research Journal, 2010)
The present study on body weight and feed efficiency for growth was carried out on 112 turkeypoults from day of hatch to 28 weeks of age during May to November 2002 at Poultry ResearchUnit of Regional Agricultural Research Station (RARS)-Parwanipur. Layer starter rationsupplemented with 6% fish meal + 0.3% lysine + 0.125% methonine was fed up to 8 weeks ofage, then after layer finisher diet was fed. The body weight, feed consumption was observed at 4weekly interval and feed efficiency and economics of rearing period in terms of income overfeed and poults cost was calculated. Significant increase in body weight was recorded up to 28weeks in male and 20 weeks in female. Male turkey had significantly higher body weight thanthat of female in all ages. Feed efficiency is best at earlier age but up to 16 weeks it is 3.77 formale after that it detoriates progressively. Male turkey exhibited better feed efficiency than thatof female for all weeks. Significantly higher return per bird was obtained from male than that offemale in all age. The profit per bird for both male and female was found maximum in 16 weeksof rearing, followed by 20 weeks and 24 weeks. Therefore, instead of waiting for highest bodyweight, it is better to sell turkey at 16 to 20 weeks of age to take maximum advantage of higherweight gain, higher efficiency of feed utilization and higher profit.Key words: Economics; feed utilization; growth; rearing period; turkeyDOI: 10.3126/narj.v6i0.3369Nepal Agriculture Research Journal Vol.6 2005 pp.84-88